2005
DOI: 10.1080/00343400500327943
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, economic growth and regional development

Abstract: Iyer S., Kitson M. and Toh B. (2005) Social capital, economic growth and regional development, Regional Studies 39 , 1015-1040. This paper examines the relationships between social capital, economic performance and regional development, and it stresses the complexity and variability across space of such relationships. In contrast to the conventional macroeconomic approach of using indicators of social capital in formal growth models, what is required is a more nuanced analysis that evaluates the impact of soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(197 citation statements)
references
References 43 publications
6
180
1
10
Order By: Relevance
“…They concluded that disaggregation at regional levels reveals information that remains elusive at the national level (Fazio, Lavecchia 2013, p. 315). In line with this conclusion, Iyer et al (2005) suggested a shift towards a more region-specific approach to social capital.…”
Section: Empirical Studies On Social Capital and Economic Well-beingsupporting
confidence: 57%
“…They concluded that disaggregation at regional levels reveals information that remains elusive at the national level (Fazio, Lavecchia 2013, p. 315). In line with this conclusion, Iyer et al (2005) suggested a shift towards a more region-specific approach to social capital.…”
Section: Empirical Studies On Social Capital and Economic Well-beingsupporting
confidence: 57%
“…This is significantly different from the type of social or relational capital stemming from the social norms and customs present in a particular region (Capello and Faggian, 2005;Tura and Harmaakorpi, 2005). These social norms and customs are embedded in the social environment, and the trustworthiness of any environment is often tacit and specific to each community (Iyer et al, 2005;Lorenzen, 2007). However, as Putnam finds, although communities, especially business communities, are now more networked than ever, they actually possess less social capital, and 'in some ways social capital may be economically counterproductive' (Putnam, 2000, p. 322).…”
Section: Network Capitalmentioning
confidence: 99%
“…Some scholars have pointed to networks endowed with social capital -in the form of interpersonal relationships -as a key lubricator of knowledge spillovers (Iyer et al, 2005;Tura and Harmaakorpi, 2005;Hauser et al, 2007;Lorenzen, 2007;Walter et al, 2007;Tappeiner et al, 2008;Cantner et al, 2009;Vorley et al, 2012). In its fundamental form, social capital concerns the capacity and capability of individuals to mobilise their network to enhance personal returns usually within place-bound environments.…”
Section: Network Capitalmentioning
confidence: 99%
“…Some scholars have pointed to networks endowed with social capital -in the form of interpersonal relationships -as a key lubricator of knowledge spillovers (Iyer et al 2005;Tura and Harmaakorpi 2005;Hauser et al 2007;Lorenzen 2007;Walter et al 2007;Tappeiner et al 2008;Cantner et al 2010;Vorley et al 2012). However, although social capital may explain a degree of knowledge flow within a particular region, it does not necessarily account for the large proportion of the flow of economically beneficial knowledge (Bathelt et al 2004;Weterings and Ponds 2009;Huber 2012).…”
Section: A Network-based View Of Innovationmentioning
confidence: 99%